CINEMA NA ESCOLA: COMPREENDENDO AS PRODUÇÕES DE SENTIDO NOS TEXTOS (ORAIS E ESCRITOS) DAS CRIANÇAS DO CICLO DE ALFABETIZAÇÃO - Ramos, Santiago Daniel Hernandez Piloto (2020)
The thesis integrates studies in the field of literacy developed by the line of research Educação e Linguagem, of the Graduate Program in Education at the Universidade Federal do Espírito Santo. In general, the research has as its theme the relationship b